A metal-free additive texturization method used for diamond-wire-sawn multi-crystalline silicon wafers. (1st November 2020) - Li, Likai; Jin, Hao; Wang, Qi; Yang, Deren; Wang, Lei
Abstract: Diamond-wire-sawn (DWS) technique has been widely applied in PV industry. However, this technique still has a big challenge when it is used for multi-crystalline silicon (mc-Si) because its reflectivity of DWS mc-Si etched by the conventional acid etching solution (HF/HNO3 /H2 O system) is quite higher. This paper proposes a metal-free additive texturization method, in which polyethylene glycol (PEG) is added to the HF/HNO3 /H2 O system to reduce the reaction rate of silicon wafers and improve the wettability of the etching liquid and the surface of mc-Si wafers. The etching points will gradually turn into nanopores instead of worm-like structures due to low reaction rates. Those nanopores form a gradually changed refractive index between silicon and air, which immensely reduces the surface reflectivity of mc-Si wafers. The mc-Si wafers processed in the experiment have an average surface reflectivity of about 16.9% in the wavelength range of 300–1100 nm, which is generally lower than the mc-Si wafers etched by the conventional acid etching process. This technical route has been applied to fabricate the 156 mm × 156 mm DWS mc-Si solar cells, and finally, the conversion efficiency of 19.39% has been obtained. Moreover, this approach matches well with the current PV industrial processes, showing a promising prospect.